Performance analysis of a DWDM optical transport network with crosstalk - Md. Fahmid-ul-Islam; Chowdhury, Md. Atiqul Haque; Hussain, Muntakim (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.